Do International Students Benefit from Their US Study-Abroad Experience? - Esaki-Smith, Anna (International Higher Education, 2022)
Increasingly, international students pursue study abroad to gain skills that will enhance their employment prospects upon graduation. Host destinations such as the United Kingdom, Australia, and Canada not only offer pathways connecting education to a professional future, but data that quantifies how international graduates have benefited from their overseas study experiences. The United States comes up short in both those areas. Can it catch up?